2006
DOI: 10.1136/ard.2005.043471
|View full text |Cite
|
Sign up to set email alerts
|

Low grade radiographic sacroiliitis as prognostic factor in patients with undifferentiated spondyloarthritis fulfilling diagnostic criteria for ankylosing spondylitis throughout follow up

Abstract: Objective: To determine the rate and factors associated with ankylosing spondylitis in a cohort of patients with undifferentiated spondyloarthritides (SpA). Methods: 62 consecutive patients with undifferentiated SpA seen between 1998 and 1999 underwent clinical and imaging evaluations throughout follow up. The main outcome measure was a diagnosis of ankylosing spondylitis. Results: 50 patients with peripheral arthritis (n = 35) and inflammatory back pain (n = 24) (26 male; mean (SD) age at onset, 20.4 (8.8) ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 20 publications
4
38
1
3
Order By: Relevance
“…Based on our results, we hypothesize that in patients with early axial SpA, male sex may be a risk factor for the development of radiographic sacroiliitis, and, therefore, for the evolution to AS. This hypothesis is consistent with the observed male predominance in AS, although a rather balanced sex distribution is often reported in uSpA (34)(35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Based on our results, we hypothesize that in patients with early axial SpA, male sex may be a risk factor for the development of radiographic sacroiliitis, and, therefore, for the evolution to AS. This hypothesis is consistent with the observed male predominance in AS, although a rather balanced sex distribution is often reported in uSpA (34)(35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 79%
“…A role for CRP in the development of definite radiographic sacroiliitis was also suggested in the small study by Huerta-Sil et al (38) in 50 patients with uSpA; after 3-5 years, uSpA evolved to AS in 21 of those patients. CRP was also associated with syndesmophytes in the spines of GES-PIC patients with AS.…”
Section: Discussionmentioning
confidence: 90%
“…In 2 shorter followup studies, the proportion of patients fulfilling AS criteria 24 and 28 months after onset were 10% 22 and 36% 23 , respectively. In the Schattenkirchner and Krüger study 24 , the percentage reached 25% within 2 to 6 years, versus Huerta-Sil's finding of 42% by 3 years after symptom onset 25 . Two further studies 16,26 found AS in 25% and 36% by 5 years after onset.…”
Section: Editorialmentioning
confidence: 90%
“…Diagnosis varied from "HLA-B27-negative associated oligoarthritis" 24 to "possible ankylosing spondylitis" 16 , "possible SpA" 26 , and "undifferentiated SpA" 17,22,25 . Disease duration in various studies extended more than 10 years (i.e., the sum of the duration of the disease at baseline and the duration of followup); therefore, diagnosis of USpA does not necessarily mean early or recent SpA.…”
Section: Editorialmentioning
confidence: 99%
“…Nevertheless, a subgroup of patients in a Dutch cohort developed structural changes rather early in the disease course; 20% of the patients with a history of inflammatory back pain of Ͻ2 years in duration had chronic structural changes in the SI joints (27). Although low-grade radiographic sacroiliitis has been proposed as a prognostic factor for the development of AS in patients originally classified as having undifferentiated SpA, only a minority of patients with nr-axSpA seem to develop definitive AS (28).…”
mentioning
confidence: 99%